Researching the Heartland of Pentecostalism: Latin Americans at Home and Abroad - Freston, Paul (Fieldwork in religion, 2008)
Latin America is undergoing a singular process of Christian pluralization from within and from the bottom up. It is thus a unique site for globalizing the US-European debate on religion and modernity. Pentecostalism has been the engine of religious change in Latin America, introducing a new model of the religious field. This article examines the relationship between the simultaneous growth of Pentecostalism and "no religion." Latin America is also an important site for exploring the validity of controversial interpretations of the political implications of global southern Protestantism, with regard to geopolitics, democracy, urban violence and human rights. This paper also asks what light is thrown by Latin American Pentecostalism on the historical correlation between Protestantism and economic development, and by Latin American Pentecostal missionaries on the global debate about the rights and wrongs of proselytism. The conclusion discusses how the approaching ceiling on Pentecostal growth will change its sociological characteristics.